The Relationship between Social Support and Relapse among Former Drug Addict - Razali, Asbah; Ani, Fauziah; Mohd Tohar, Siti Nor Azhani (Journal of Social Transformation and Regional Development, 2019)
This study aims to identify the relationship between the social support and relapse among former drug addicts. This study involves 242 former addicts that completed their treatment and rehabilitation period and utilises two instruments, the Inventory of Drug-Taking Situations, (IDTS) by Annis and Martin (1985) and the Social Provisions Scale (SPS) by Russell and Cutrona (1984). This study uses descriptive statistical method or frequency to see the percentage for the demographic factor, while the inferential statistical method such as the Pearson correlation were used to test the research question. The Pearson correlation analysis shows a significant relationship between social support and to relapse. The results conclude that the friends and societal could influence the inclination to relapse among former addicts. In summary, social become a source of rationalization for various types of devian behaviour and affecting former drug addicts to decide to relapse.